Traditional Food Arrangements as Expressions of Traditional Culture - Ni Komang Irma Adi Sukmaningsih; Ni Ketut Supasti Dharmawan; Marwanto Marwanto (Faculty of Law, Musamus University, 2019)
Traditional Cultural Expressions have basically been protected through national law, but in their regulation traditional food is not included as part of Traditional Cultural Expressions even though traditional food is one of Indonesia's traditional cultures that also characterizes the Indonesian Nation. For this reason, it is important to study the norms that occur in this study. The purpose of this study is to analyze the traditional food protection arrangements as traditional cultural expressions and the legal consequences that will occur if a traditional food is not listed as part of traditional cultural expressions. The method in this study uses a type of normative juridical legal research with a statute approach that focuses on the study of statutory regulations regarding legal issues in this study. The sources of legal materials in this study consist of primary, secondary, and tertiary legal materials. The results of this study indicate that traditional food regulation has not been regulated as Traditional Cultural Expressions in the law in force in Indonesia precisely in Law No. 28 of 2014 concerning Copyright. The absence of arrangements related to traditional food as Traditional Cultural Expressions results in foreign parties or other countries easily recognizing the tradition, so it is necessary to regulate traditional food as Traditional Cultural Expressions.